(untitled) (Journal of Dhaka National Medical College & Hospital, 2018)
Background: Annona squamosa is a fruit tree with long history of traditional use. Leaves of Annona squamosa have been reported to have gastroprotective effect. Objectives: The present work was conducted to evaluate the gastroprotective effect of Annona squamosa leaf on ethanol induced gastric ulcer in comparison to omeprazole. Study Design: To observe the gastroprotective effect of Annona squamosa leaf on ethanol induced gastric ulcer in rats an experimental study was done. Place and period of study: The study was conducted during July 2015 to June 2016 in the Department of Pharmacology & Therapeutics, Dhaka Medical College, Dhaka. Materials and Methods: A total number of 30 healthy Long Evan rats were used in this study. The experiment was divided into 2 parts: Experiment I and Experiment II. Experiment I was comprised of 12 rats: Group-A and Group-B having 6 rats in each group. Ulcer was produced by administration of absolute ethanol (1 mg/kg body wt.) in Group-B where Group-A served as control group and was provided with distilled water (5 ml/kg body wt.). All the rats were sacrificed after 60 minutes of ethanol administration, to confirm gastric ulcer by histopathology. Experiment II was comprised of 18 rats: Group-C, Group-D and Group-E having 6 rats in each group. Group-C served as disease control group and provided with distilled water (5 ml/kg body wt.). Group-D was provided with aqueous extract of Annona squamosa (500 mg/kg body wt.) and Group-E was provided with omeprazole suspension (10 mg/kg body wt.). After 10 days of treatment, animals were fasted for 24 hours. Then 1 ml of absolute ethanol (1 mg/kg body wt.) was administered and after 60 minutes all rats were sacrificed. Gross and microscopic examinations were performed to evaluate the results. Results: The mean ± SD of Lesion Index in Group C, Group D and Group E were 37.71 ±7.47 mm, 6.16 ±1.42 mm and 3.33 ±0.64 mm respectively. Statistically highly significant of difference was observed between Group C and Group D (P value < 0.001), between Group C and Group E (P value <0.001) and between Group D and Group E (P value < 0.05). It was observed that Absolute ethanol caused marked gastric damage in negative control group which was prevented in omeprazole suspension and aqueous extract of Annona squamosa treated groups significantly. The protective effect was maximum with omeprazole followed by aqueous extract of Annona squamosa (500 mg/kg body wt.). Aqueous extract of Annona squamosa showed significant protection against ethanol induced gastric ulcer in rats as compared to omeprazole. Conclusion: In conclusion this study establishes that Annona squamosa (Atafol) extract has gastro-protective ability following consumption of ethanol, in comparison to omeprazole. J. Dhaka National Med. Coll. Hos. 2018; 24 (01): 33-37